Wilson, E. D y F. M. Peter. 1988. Biodiversity. National Academy Press. Washington, D. C. 521 p. - Soto, Ricardo (Revista de Biología Tropical, 1988)
CIMAR y Escuela de Biología, Universidad de Costa Rica, San José, Costa Rica